THEORETICAL BASIS OF THE DEVELOPMENT OF SPECIAL ECONOMIC ZONES IN THE REGION (Marketing Journal, 2025)
This article is devoted to studying the theoretical foundations of the development of Special Economic Zones (SEZs) in regions. The concept of SEZs, as well as the economic and legal theories of their establishment and development, are analyzed. In additio n, the article examines the impact of SEZs on regional economies, attracting investments, and creating jobs, thereby contributing to economic growth. The research is aimed at identifying the theoretical foundations of SEZs and assessing their role in regio nal economic development.
Keywords: special economic zones; regional development; regional economy; theoretical foundations; investment attraction; job creation; economic growth; tax incentives; industrial zones. № 1 183